Disaster-Resilient Village Development: Implementing Landslide Detection Tools and a Solar Cell-Based Coffee Processing System - Adi Sucipto; Hesti Respatiningsih; Rusmiyatun Rusmiyatun; Suyitno Suyitno; Murry Harmawan Saputra; Jeki Mediantari Wahyu Wibawanti (Jurnal Pemberdayaan Masyarakat, 2026)
This community service article talks about the results of the Kolaborasi Sosial Membangun Masyarakat (KOSABANGSA) program in Donorejo, Purworejo. The program combines landslide Early Warning System (EWS) technology with solar-powered coffee processing after harvest to help reduce disaster risk and boost the economy. The program's goal was to make communities more resilient to hydrometeorological hazards while also making local coffee more productive and easier to sell by sharing technology and building capacity through collaboration. The intervention was carried out using a participatory, descriptive, qualitative method. It included socialization, technical training, technology installation, focused mentoring, and long-term evaluation with the FPRB and Bangun Semi Farmers' Group. The results showed that participants made big strides in being ready for disasters, running their businesses, getting to alternative energy sources, and coming up with new products. The program comes to the conclusion that people should be involved in their communities and use the right technology.